Delphi study of risk to individuals who disclose personal information online. (February 2023) - Haynes, David; Robinson, Lyn
A two-round Delphi study was conducted to explore priorities for addressing online risk to individuals. A corpus of literature was created based on 69 peer-reviewed articles about privacy risk and the privacy calculus published between 2014 and 2019. A cluster analysis of the resulting text-base using Pearson's correlation coefficient resulted in seven broad topics. After two rounds of the Delphi survey with experts in information security and information literacy, the following topics were identified as priorities for further investigation: personalisation versus privacy, responsibility for privacy on social networks, measuring privacy risk, and perceptions of powerlessness and the resulting apathy. The Delphi approach provided clear conclusions about research topics and has potential as a tool for prioritising future research areas.